Tax revenue mobilization in conflict-affected developing countries - Vanessa van den Boogaard; Wilson Prichard; Nikola Milicic; Matthew Benson (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
How does conflict affect tax revenue mobilization? This paper uses a newly updated dataset to explore longitudinal trends of tax revenue mobilization prior to, during, and after conflict periods in a selection of conflict-affected states since 1980. This medium-N trend analysis is complemented by prototypical case study analysis, which provides greater insight into the relationship between tax revenue performance over time and the characteristics of the conflicts in question. Offering detailed snapshots of tax experiences prior to, during, and after conflict, this paper provides an empirical counterpoint to theories about the role of taxation in war-making and state building.
Keywords: H20; H11; 330; taxation; revenue mobilization; conflict